Detrusor underactivity and the underactive bladder: Symptoms, function, cause—what do we mean? ICI‐RS think tank 2014. Issue 2 (February 2016) - Smith, Phillip P.; Birder, Lori A.; Abrams, Paul; Wein, Alan J.; Chapple, Chris R.
Abstract : Impaired bladder emptying is a well‐recognized cause of lower urinary tract symptoms. However, the symptoms produced do not always relate to voiding, and may include frequency, urgency and incontinence. Conversely, the etiology of symptoms of disturbed voiding is not necessarily dependent upon objectively impaired voiding. Terms including underactive bladder, detrusor underactivity, and impaired contractility describe aspects of these problems, and have been used somewhat interchangeably. It is possible that the present lack of effective therapy in many cases relates to both etiologic and diagnostic uncertainty stemming from terminologic imprecision. Detrusor underactivity has a standardized definition, unlike underactive bladder and impaired contractility. The relationships of symptoms, function, and cause were the focus of a 2014 ICI‐RS Think Tank entitled Does Detrusor Underactivity Exist, and if so it is neurogenic, myogenic, or both? This review presents a summary of the problem and the Think Tank conclusions. A terminologic hierarchy and specific research goals are presented. Neurourol. Urodynam. 35:312–317, 2016 . © 2016 Wiley Periodicals, Inc.